2006
DOI: 10.1196/annals.1353.026
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Phenylethanolamine N‐Methyltransferase in Pheochromocytomas from Patients with von Hippel–Lindau Syndrome and Multiple Endocrine Neoplasia Type 2

Abstract: Pheochromocytomas in multiple endocrine neoplasia type 2 (MEN-2) express phenylethanolamine N-methyltransferase (PNMT), the enzyme that catalyzes conversion of norepinephrine to epinephrine, whereas those in von Hippel-Lindau (VHL) syndrome do not. Consequently, pheochromocytomas in MEN-2 produce epinephrine, whereas those in VHL syndrome produce mainly norepinephrine. This study examined whether transcription factors known to regulate expression of PNMT explain the different tumor phenotypes in these syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
(28 reference statements)
4
17
0
Order By: Relevance
“…Our results verified PNMT hypermethylation previously reported in SDHBrelated PPGLs (2). PNMT hypomethylation in RET-and NF1-and hemimethylation in VHL-related PPGLs is highly consistent their associated neurochemical phenotypes (2,20,29). However, this model does not explain why other "cluster 1" tumors do not display an adrenergic phenotype, even when PNMT is hemimethylated.…”
Section: Discussionsupporting
confidence: 71%
“…Our results verified PNMT hypermethylation previously reported in SDHBrelated PPGLs (2). PNMT hypomethylation in RET-and NF1-and hemimethylation in VHL-related PPGLs is highly consistent their associated neurochemical phenotypes (2,20,29). However, this model does not explain why other "cluster 1" tumors do not display an adrenergic phenotype, even when PNMT is hemimethylated.…”
Section: Discussionsupporting
confidence: 71%
“…It was estimated that about 30% of sporadic aPCA and eFPGL have a similar gene expression signature to VHL/SDHX tumours and the other 70% to NF1/RET (53). Interestingly, the differences in gene expression profiles can be correlated with the tendency of VHL and SDHX tumours to produced mainly noradrenaline, and RET/NF1 tumours to be adrenergic (56). Recently, Burnichon et al (55) have demonstrated that the gene expression profiling can be used to identify which subset of sporadic tumours are likely to harbour somatic VHL or RET mutations and so provide a basis for potential personalised therapies.…”
Section: The Molecular Pathophysiology Of Inherited Phaeochromocytomamentioning
confidence: 87%
“…These findings fit with others indicating that familial pheochromocytomas develop by a single pathway linking mutations in disease-causing genes to failure of apoptosis after withdrawal of growth factors during chromaffin cell development. 14 As advanced elsewhere in this volume by Huynh et al, 15 epinephrine-producing tumors in MEN 2A are hypothesized to develop due to susceptibility of more fully developed PNMT-expressing chromaffin cells to the effects of activating RET mutations, whereas norepinephrine-producing pheochromocytomas in VHL syndrome develop from neural crest progenitors before their final development into differentiated epinephrine-producing adrenal chromaffin cells.…”
Section: Discussionmentioning
confidence: 99%